2018
DOI: 10.1021/acsnano.7b05813
|View full text |Cite
|
Sign up to set email alerts
|

Under-Oil Switchable Superhydrophobicity to Superhydrophilicity Transition on TiO2 Nanotube Arrays

Abstract: Recently, smart interfacial materials that can reversibly transit between the superhydrophobicity and superhydrophilicity have aroused much attention. However, all present performances happen in air, and to realize such a smart transition in complex environments, such as oil, is still a challenge. Herein, TiO nanotube arrays with switchable transition between the superhydrophobicity and superhydrophilicity in oil are reported. The switching can be observed by alternation of UV irradiation and heating process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 59 publications
1
67
0
Order By: Relevance
“…Nevertheless, conventional ceramic materials with high surface energy exhibit low repellence for both water and oil droplets [8], and thus failed in selectively separation for immiscible oil/water mixture which is governed by interfacial phenomenon [9]. Although lots of materials with tunable surface wettability have been reported by controlling surface chemical composition and microstructure alone, or together [10][11][12][13], templatefree ceramic nanofibrous membrane with super surface wettability is still rarely reported. This is possibly due to the difficulties in tuning the surface wettability for a chemicaland physical-stable materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, conventional ceramic materials with high surface energy exhibit low repellence for both water and oil droplets [8], and thus failed in selectively separation for immiscible oil/water mixture which is governed by interfacial phenomenon [9]. Although lots of materials with tunable surface wettability have been reported by controlling surface chemical composition and microstructure alone, or together [10][11][12][13], templatefree ceramic nanofibrous membrane with super surface wettability is still rarely reported. This is possibly due to the difficulties in tuning the surface wettability for a chemicaland physical-stable materials.…”
Section: Introductionmentioning
confidence: 99%
“…The second is the superhydrophilicity. [ 55–57 ] The contact angle test results demonstrate that the formed NiO on the surface of the laser‐treated Ni foam sample interacts with the water through the hydrogen bond, enhancing the mass transfer of glucose, since the whole experimental processes were carried out in aqueous solution. The third is the good conductivity of laser‐treated Ni foam.…”
Section: Resultsmentioning
confidence: 99%
“… 73 Recently, superhydrophilic/-hydrophobic fabric with self-propelled directional wetting patterns controlled by UV illumination and temperature has been successfully created by a one-step coating process involving nano-TiO 2 . 74 Random frameworks can also be generated by chemical methods such as etching/oxidation, layer-by-layer, sol–gel methods, and so on. Zhu et al 75 reported a simple three-step treatment method to generate superamphiphilic silicon wafer surfaces with contact angles near 0° for both water and typical organic liquids.…”
Section: Current Developments and Challenges Of Designs Of Superhydromentioning
confidence: 99%